Histología y morfometría del ojo del pez dulceacuícola Paracheirodon axelrodi (Characiformes: Characidae) - O. Tovar, Mario (2009)
The visual system of Teleost fishes has a wide range of adaptations. The eye has suffered modifi-cations, mainly towards better sensitivity and visual resolution according to specific environmental conditions. In that way, this organ is so important for survival. In spite of being the most commercialized Orinoquía species, and one of the most important ornamental fish worldwide, there are almost no studies on the communication systems of P. axelrodi (including vision). We studied the eye in ten individuals of P. axelrodi, with a mean total length of 2.7 cm (SD= 0.2, n= 20). We measured eye relative size (TRO) after sacrifice. Heads were processed for hematoxylin-eosin, and 8 μm thick sections were obtained. Images were digitalized for histological identi-fication and morphometrics. The relation between TRO and body length was 9.8% (SD= 1.1, n= 20); lens was spherical with a relative size of 64.3% (SD= 4.9, n= 20). Rete mirabilis choroid was composed mainly by capil-laries, while sclera was composed of cartilaginous tissue. Retina with eight layers and two membranes. An areae centrales was observed in the posterior retina. Iris covered by a simple cubic epithelium. Cornea of endotelial tissue with two membranes. Pupil almost circular, with a naso-caudal elongation. Measures of retina thickness were as follows: lateral retina 144.5 μm (SD= 5.4, n= 20), temporal retina 210.4 μm (SD= 14.8, n= 20). Lens measurements were: dorso-ventral 759.6 μm (SD= 31.7, n= 20), antero-posterior 763.4 μm (SD= 30.7, n= 20). Cornea thickness was 27.6 μm (SD= 4.3, n= 20); iris thickness was 18.9 μm (SD= 1.9, n= 20); rete mirabilis choroid 22.2 μm (SD= 3.2, n= 20) and sclera: 15.9 μm (SD= 1.2, n= 20). This species has a typical Teleost eye conformation. The retina was thicker in the posterior area, probably related to the presence of neuron groups. This modification allows for a better sharpness and visual resolution. The TRO, areae centrales in the retina, and thin cornea, suggests the need of a well developed visual system resulting from a predatory diet.